Efektifitas Pengetahuan Lansia Terkait Hipertensi Untuk Mencegah Terjadinya Penyakit Komplikasi Melalui Penyuluhan Di Gampong Jurong Binje Jangka Buya Pidie Jaya - Ambia Nurdin; Nurhaliza Nurhaliza; Muhammad Muhammad; Amiruddin Amiruddin; Zakiyuddin Zakiyuddin; Ricky Dear Fitria; Fauzi Aldina; Hendra Cipta; Muhammad Haikal (Pusat Riset dan Inovasi Nasional, 2023)
Hypertension or high blood pressure is one of the main health problems in every country because it can cause heart disease and deadly brain stroke. Hypertension is seen as a serious health problem because we often don't realize it comes with few if any real symptoms. This disease can continue to get worse without realizing it to a level that threatens the life of the sufferer. Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest/calm. This study used a pre-experimental design method with the type of one group pretest-posttest design. The target in this study were the elderly in Jurong Binje Village, Jangka Buya District, Pidie Jaya Regency. The questionnaire in this study was used to examine the effect of counseling about hypertension on increasing the knowledge of the elderly in Jurong Binje Village, Jangka Buya District, Pidie Jaya Regency. The number of samples taken was 15 elderly people. It is known that most of the respondents were female as many as 10 respondents with a percentage of 66.7%, while most of them were aged 55-60 years as many as 9 respondents with a percentage of 60%. The highest level of knowledge of the elderly before being given counseling was in the moderate category, 5 people (33.3%). The highest level of knowledge of the elderly after being given counseling was in the high category, 15 people (100%). The average knowledge level of the elderly before being given counseling was 1.67 and after being given counseling was 1.00. From these results it can be concluded that there were positive results from the counseling process carried out.